URGENSI DIGITALISASI DALAM TRANSFORMASI KURIKULUM UNTUK MENGHASILKAN TENAGA KERJA BIDANG TEKNIK ELEKTRO YANG KOMPETITIF DI ERA INDUSTRI - Meriani Meriani; Zakia Lutfiani; Sucipto (Jurnal Saintifik (Multi Science Journal), 2025)
The industrial world is currently experiencing a massive disruption triggered by the Fourth Industrial Revolution. The electrical engineering sector, as the backbone of energy infrastructure and manufacturing, demands a workforce that is not only skilled manually but also digitally proficient. This article examines the importance of integrating digitalization into the curriculum at Raflesia Polytechnic in Curup. The study focuses on the use of design software (CAD), the implementation of the Internet of Things (IoT), and industrial automation systems. The analysis results indicate that digitalization can improve learning efficiency by up to 40% and expand the employability of graduates in the global job market.